Ah, my title ! I'm sorry ! I was looking at the wrong question. Heh. If f (x/x+1) = 1/x, x cannot be = 0, 1, and 0 <= theta <= pi/2, then simplify f (1/cos^2theta) Thanks in advance : D
Last edited by ahling; Jul 28th 2008 at 03:48 PM.
Follow Math Help Forum on Facebook and Google+
Originally Posted by ahling Ah, my title ! I'm sorry ! I was looking at the wrong question. Heh. If f (x/x+1) = 1/x, x cannot be = 0, 1, and 0 <= theta <= pi/2, then simplify f (1/cos^2theta) Thanks in advance : D For a non exeptional , let: so: so (for non-exceptional ): Now simplify. RonL
Originally Posted by ahling Ah, my title ! I'm sorry ! I was looking at the wrong question. Heh. If f (x/x+1) = 1/x, x cannot be = 0, 1, and 0 <= theta <= pi/2, then simplify f (1/cos^2theta) Thanks in advance : D f (x/x+1) = 1/x Now in place of x put 1/x f (1/x+1) = x f (1/cos^2theta)=f (1/1-sin^2theta)=-sin^2theta where sintheta cannot be = 0, 1,
Last edited by nikhil; Jul 29th 2008 at 03:43 AM.
Originally Posted by nikhil f (x/x+1) = 1/x Now in place of x put 1/x f (1/x+1) = x f (1/cos^2theta)=f (1/1-sin^2theta)=-sin^2theta where sintheta cannot be = 0, 1, Like I should have told the OP use brackets to remove the ambiguity of expressions like 1/x+1 or x/x+1. RonL
View Tag Cloud